Applying the Potter Box Moral Model in Social Media Use: A Study of Sungai Kunjang Flat Residents through an Islamic Ethical Lens - Oktariyani, Oktariyani; Shobah, Sy Nurul; Inayah, Sitti Syahar (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The background of this study explains that the Potter box moral model examines the ethical considerations taken into account by social media users, particularly residents of Sungai Kunjang Flat, when applying the Potter box moral model in everyday social media use. This study uses a qualitative method. This means that, in general, it can be used for research on people's lives, history, behaviour, concepts, phenomena, social problems, and others. The theory used in this study is the theory of communication, including communication ethics and the nature of the media, which is supported by the Potter Box theory, utilising four quadrants: facts or situation descriptions, identification of values, ethical principles, and loyalty or responsibility. The purpose of this study was to describe the moral potter's box model in the context of social media use among residents of Sungai Kunjang Flat. The results of this study indicate that the potter box is a moral consideration that benefits social media users, specifically the residents of Sungai Kunjang Flat. The Potter box uses a step that consists of four steps: situation description, identification of values, ethical principles, and loyalty/responsibility. The first step is to describe the situation. Flat residents use their social media to stay informed about current issues or events, such as crime, health, and other concerns. The second step, following up on the problems identified in the first step, involves re-checking the truth value to determine whether the news and issues are accurate. The next step explains how the residents of the flat apply ethical principles in their use of social media. The final step involves determining someone's loyalty.